1999
DOI: 10.1088/0957-4484/10/3/318
|View full text |Cite
|
Sign up to set email alerts
|

Laser-assisted deposition of bacteriorhodhopsin assemblies

Abstract: Supramolecular assemblies of bacteriorhodhopsin (bR) have been formed by incorporating bR in a matrix of L-α-phosphatidylcholine distearoyl (DSPC) molecules. The preformed assemblies have been physically lifted and deposited onto solid substrates by the laser-assisted deposition (LAD) technique. The bR assemblies thus deposited have been characterized using a variety of techniques like absorption studies, optical microscopy and x-ray diffraction. The structural and functional properties of the bR assemblies ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…They showed that the constituent molecules in the deposited material displayed characteristic native properties and the assemblies retained their morphological identity. In a following publication, the same authors reported the growth of supramolecular assemblies consisting of the photosensitive protein bacteriorhodhopsin (bR) embedded in the lipid l -α-phosphatidylcholine distearoyl (DSPC) by PLD . Again the authors found that the structural and functional properties of the bR+DSPC assemblies were preserved by PLD.…”
Section: 34 Pld Of Biomaterialsmentioning
confidence: 98%
“…They showed that the constituent molecules in the deposited material displayed characteristic native properties and the assemblies retained their morphological identity. In a following publication, the same authors reported the growth of supramolecular assemblies consisting of the photosensitive protein bacteriorhodhopsin (bR) embedded in the lipid l -α-phosphatidylcholine distearoyl (DSPC) by PLD . Again the authors found that the structural and functional properties of the bR+DSPC assemblies were preserved by PLD.…”
Section: 34 Pld Of Biomaterialsmentioning
confidence: 98%
“…Phadke and Agarwal used a variation of this technique to form films of bacteriorhodhopsin and glucose oxidase. 35,36 To reduce the laser interaction with the protein, a composite target was formed containing the protein in a surfactant matrix. The surfactant was found to protect the biomaterial, and films of active protein were formed.…”
Section: Introductionmentioning
confidence: 99%
“…The infrared spectrum of the deposited material was nearly identical to the bulk, pressed target material, but a mass distribution of the deposited material was not reported. Phadke and Agarwal used a variation of this technique to form films of bacteriorhodhopsin and glucose oxidase. , To reduce the laser interaction with the protein, a composite target was formed containing the protein in a surfactant matrix. The surfactant was found to protect the biomaterial, and films of active protein were formed.…”
Section: Introductionmentioning
confidence: 99%
“…1), which allows to grow films of inorganic [22,23] as well as organic materials [24][25][26]. It has been proven that this technique is suitable for deposition of thin films of biomaterials such as DNA [27], enzymes [28] and proteins [29,30]. The femtosecond lasers due to their advantages in material processing, such as reduced thermal effects, target damage and lower ablation threshold, can be used for the transfer of biological materials [31].…”
Section: Laser Printing Of Biomaterialsmentioning
confidence: 99%